On the characterization of EM emission of electronic products: Case study for different program modes - Yuwono, Tito; Baharuddin, Mohd Hafiz; Zhivomirov, Hristo; Wahyuni, Elyza Gustri (Communications in Science and Technology, 2024)
The characterization of the EM emissions for electronic products is crucial to ensure that the emissions have met the requirements of the EMC standards. For this, a more comprehensive testing is required to get more meaningful results. While, the emergence of non-stationary emissions is a challenge to obtain valid analysis results. So far, non-stationary EM emissions is not considered and treated properly in the emission analysis. This paper presents a new method for the analysis of EM emissions from electronic devices as a case study by testing three different program modes (scenarios) of Intel Galileo board. These program modes were designed to vary processing intensity in its memory and processor. A comparison was also made between the actual situation (the presence of non-stationary signals) and the hypothetical situation with the assumption that all emissions were stationary. As a result, a significant difference was observed when the analysis considered the real scenario of a non-stationary emission. The ratio between the average autocorrelation using the proposed algorithm and the average correlation by ignoring the non-stationarity of the emission signal was 113.6 times. The study concludes that different program modes produce the different characteristics of EM emissions, making some of them non-stationary. Hence, we strongly suggest the consideration of the non-stationarity of the EM emissions in characterizing complex electronic devices.